Hydrothermally Produced Activated Carbon Impregnated with ZnO for the Adsorptive Removal of Toxic Pharmaceutical Contaminants from Aqueous Solution - Kilaru Harsha Vardhan; Hrishitha Sree; P. Senthil Kumar; B. Senthil Rathi (International Journal of Chemical Engineering)
This research explores the adsorption (AD) of diclofenac sodium (DS) onto a Hydrothermally produced activated carbon impregnated with ZnO (HTC-AC/ZnO) surface, considering various factors such as initial concentration (IC), adsorbent dose, contact time, and pH. The characterization of HTC-AC/ZnO was performed using X-ray diffractometer (XRD), scanning electron microscope (SEM), Fourier-transform infrared spectroscopy (FTIR), and nitrogen physisorption spectroscopy (BET). Tests were conducted with different adsorbent doses (0.5–4 g/L) at 303 K and various initial diclofenac concentrations (ranging from 50 mg/L to 250 mg/L) to observe their effects. Additionally, pH values were altered from 2 to 12 to study their influence on AD. Kinetic studies, thermodynamic studies, and AD isotherm models were examined. The Temkin isotherm model (TIM) was found to be the most accurate for DS-AD on HTC-AC/ZnO. For DS-AD on HTC-AC/ZnO, pseudo-first-order models (PFOM), intraparticle diffusion model (IPDM), and pseudo-second-order models (PSOM) were applied, with a correlation coefficient of 0.945, indicating a good fit for PFOM. The kinetics suggested rapid adsorption. Notably, the HTC-AC/ZnO composite exhibited consistent AD characteristics across four consecutive cycles, with a removal efficiency exceeding 99.38%. This suggests that HTC-AC/ZnO is an appropriate and economically viable adsorbent for the elimination of DS from water-based solutions. The investigation provides compelling evidence that HTC-AC/ZnO is a viable adsorbent for the effective elimination of DS from water sources.